SUSTAINABLE MARKETING STRATEGY BASED ON GREEN ECONOMY AND ENVIRONMENTALLY FRIENDLY PRODUCTS ITS IMPACT ON BUSINESS SUSTAINABILITY IN FAST-MOVING MUSLIM CONSUMER GOODS (FMMCG) SECTOR - Titis Purwaningrum; La Ode Sugianto; Wijianto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the impact of sustainable marketing strategy on business sustainability in the Fast-Moving Muslim Consumer Goods (FMCG) sector. Method: Using the resource-based view (RBV) and triple bottom line (TBL) approaches, this study explores how companies can leverage internal resources and integrate sustainability principles to create sustainable competitive advantage. Path analysis is used to test the influence of Environmental Green Product, Green Economy, and Sustainability Marketing Strategy variables on Business Sustainability. Result: The results show that Environmental Green Product and Green Economy have a positive and significant influence on business sustainability, with Green Economy having a stronger influence. In contrast, Sustainability Marketing Strategy does not have a significant direct influence on business sustainability, but plays an important role in supporting the development of environmentally friendly products and the green economy. Novelty: These findings emphasize the importance of efficient and innovative resource management in supporting environmental sustainability, as well as the need for effective marketing strategies to increase consumer awareness of the importance of environmentally friendly products. This study provides insights for FMMCG companies in implementing sustainable practices to improve long-term competitiveness and sustainability.